Tabulae cuneiformes a F. M. Th. De Liagre Böhl collectae, Leidae conservatae - Liagre Böhl, Franz Marius Theodor de, 1882-1976. (Leiden)
3 c. (1. c. [3], lxxxi y. ; 2. c. [2], xxv y. ; 3. c. [3], xxv y.)